Ocean wave-driven covalent organic framework/ZnO heterostructure composites for piezocatalytic uranium extraction from seawater - Jia-Xin Qi; Jing-Wen Gong; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Xin Liu; Jin-Lan Liu; Xiao-Juan Chen; Ru-Ping Liang; Jian-Ding Qiu (Nature Communications)
Abstract Piezoelectric catalysis possesses the potential to convert ocean wave energy into and holds broad prospects for extracting uranium from seawater. Herein, the Z-type ZnO@COF heterostructure composite with excellent piezoelectric properties was synthesized through in situ growth of covalent organic frameworks (COFs) on the surface of ZnO and used for efficient uranium extraction. The designed COFs shell enables ZnO with stability, abundant active sites and high-speed electron transport channels. Meanwhile, the interface electric field established in the heterojunctions stimulates electron transfer from COFs to ZnO, which break the edge shielding effect of the ZnO’s metallic state. Additionally, the polarization of ZnO is enhanced by heterogeneous engineering, which ensures the excellent piezocatalytic performance. As a result, ZnO@COF achieves an ultra-high efficiency of 7.56 mg g−1 d−1 for uranium extraction from natural seawater driven by waves. In this work, we open an avenue for developing efficient catalysts for uranium extraction from seawater.